2015
DOI: 10.3390/nano5020737
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Gas Sensing Properties of Ag@α-Fe2O3 Core–Shell Nanocomposites

Abstract: Ag@α-Fe2O3 nanocomposite having a core–shell structure was synthesized by a two-step reduction-sol gel approach, including Ag nanoparticles synthesis by sodium borohydride as the reducing agent in a first step and the subsequent mixing with a Fe+3 sol for α-Fe2O3 coating. The synthesized Ag@α-Fe2O3 nanocomposite has been characterized by various techniques, such as SEM, TEM and UV-Vis spectroscopy. The electrical and gas sensing properties of the synthesized composite towards low concentrations of ethanol have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(28 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…The enhanced ethanol response was attributed mainly to a wider depletion layer on the CuO/ZnO surface resulting from the formation of p-n hetero-junctions between the p-CuO nanoparticles and n-type ZnO nanorods. New nanostructures in which metals as the core and metal oxides as the shell structure are assembled into a single metal@metal oxide core-shell nanostructure have been also investigated for high performances ethanol sensors [45]. These nanostructures not only combine the properties of both noble metals and metal oxides, but also bring unique synergetic functions in comparison with single-component materials and shows superior performances for VOCs detection [118].…”
Section: Ethanol Sensorsmentioning
confidence: 99%
“…The enhanced ethanol response was attributed mainly to a wider depletion layer on the CuO/ZnO surface resulting from the formation of p-n hetero-junctions between the p-CuO nanoparticles and n-type ZnO nanorods. New nanostructures in which metals as the core and metal oxides as the shell structure are assembled into a single metal@metal oxide core-shell nanostructure have been also investigated for high performances ethanol sensors [45]. These nanostructures not only combine the properties of both noble metals and metal oxides, but also bring unique synergetic functions in comparison with single-component materials and shows superior performances for VOCs detection [118].…”
Section: Ethanol Sensorsmentioning
confidence: 99%
“…Owing to their unique physical and chemical properties, they are widely used in various areas of science and technology, such as surface-enhanced Raman spectroscopy [3], catalysts [4], anti-bacterial materials [5], sensors [6], lubricating materials [7], and so on, with exponentially increasing production. As the properties of Ag NPs depend on their sizes, up to now, various methods, such as spray pyrolysis synthesis [8], microwave irradiation synthesis [9], DC arc thermal plasma synthesis [10], chemical synthesis [11], hydrothermal synthesis [12], UV irradiation synthesis [13], sonochemical synthesis [14], laser ablation synthesis [15], thermal decomposition synthesis [16], atom beam-sputtering synthesis [17], and so forth, have been employed to prepare Ag NPs with different sizes and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…As the least expensive noble metal, silver is intensively studied as a catalytically active modifier for sensor materials based on binary semiconductor oxides [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], nanocomposites [ 29 , 30 ], as well as semiconductor materials with a perovskite structure [ 31 , 32 , 33 ]. It was shown that introducing silver makes semiconductor oxides more sensitive to hydrogen H 2 [ 9 , 11 ], carbon monoxide CO [ 17 , 28 , 32 ], hydrogen sulphide H 2 S [ 10 , 14 , 18 ], sulphur dioxide SO 2 [ 12 ], ozone O 3 [ 23 ] and nitrogen oxides NO x [ 19 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that introducing silver makes semiconductor oxides more sensitive to hydrogen H 2 [ 9 , 11 ], carbon monoxide CO [ 17 , 28 , 32 ], hydrogen sulphide H 2 S [ 10 , 14 , 18 ], sulphur dioxide SO 2 [ 12 ], ozone O 3 [ 23 ] and nitrogen oxides NO x [ 19 , 24 ]. Recently, silver has been actively explored as a modifier for gas sensors with a high sensitivity to volatile organic compounds (VOCs) [ 13 , 15 , 16 , 20 , 21 , 22 , 25 , 26 , 27 , 29 , 30 , 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%